Patients outcomes in lung adenocarcinoma transforming to small-cell lung cancer after tyrosine kinase inhibitor therapy - Shuai Wang; Yongsen Wang; Xuan Wu; Li Yang; Xiaoju Zhang (World Journal of Surgical Oncology)
Abstract Background Non-small cell lung cancer (NSCLC) transforming to small cell lung cancer (SCLC) is one of the mechanisms of resistance to tyrosine kinase inhibitors (TKIs). Cases of NSCLC transforming into SCLC have been discovered. However, we lack concentrated data on the characteristics of this population and the transformed SCLC to aid our insight of the biology and clinical value of NSCLC transforming with positive. Methods We systematically reviewed the published literatures and summarized the pathological and clinical characteristics, and the prognosis, of published cases. Results 140 patients with lung adenocarcinoma (LUAD) were included in this study, with a median age of 56.8 years. The median time from the first diagnosis of LUAD transforming to SCLC (ttSCLC) was 20.0 months. The median overall survival (mOS) after the diagnosis of SCLC was 11.0 months (95% CI, 7.41 to 14.59 months). In the univariate analysis, ever smoking (either former or current) was a promising predictor of a shorter ttSCLC (HR, 1.73; 95% CI, 1.14 to 2.62; P = 0.010). TKIs therapy administered as a second line and beyond treatment was related to a significant delay in SCLC onset compared to first-line therapy (HR, 0.62; 95% CI, 0.40 to 0.96; P = 0.031). The median progression-free survival (mPFS) on first-line platinum plus etoposide after the conversion to SCLC was 3.0 months. Female appeared to be related to worse outcomes after transformation of SCLC. Conclusion Transformed SCLC exhibited poor response to primary SCLC classic chemotherapy and immunotherapy. It carries a worse prognosis. Exploring novel therapeutic strategies for transformed SCLC is imperative.